Pemanfaatan Media Wordwall dalam Kegiatan Bimbingan Belajar Matematika KKN Universitas Hamzanwadi untuk Mengurangi Kecemasan Belajar Siswa MI NW Bagik Payung - Rina Marbela; Sri Supiyati (Universitas Mataram, 2026)
Mathematics learning anxiety is still a common problem experienced by Madrasah Ibtidaiyah students and has an impact on low self-confidence and low participation in learning activities. This community service activity aimed to reduce students’ mathematics learning anxiety at MI Bagik Payung through the use of interactive Wordwall learning media in tutoring activities conducted by KKN students of Hamzanwadi University. The activity partners were five students of MI NW Bagik Payung. The implementation method used a descriptive–participatory approach with stages of initial observation, planning, implementation, and evaluation. The instruments used were pre- and post-activity mathematics anxiety questionnaires and observation sheets. The results showed a decrease in students’ learning anxiety, indicated by increased courage, activeness, and self-confidence in solving mathematics problems. This activity shows that Wordwall media is effectively used in KKN tutoring activities as an effort to reduce mathematics learning anxiety among Madrasah Ibtidaiyah students.